Institutionalising the evaluation function: A South African study of impartiality, use and cost. (August 2019) - Blaser Mapitsa, Caitlin; Chirau, Takunda J.
Abstract: Purpose: This article explores the implications of outsourcing the evaluation function in South Africa, a context where there is a mismatch between evaluation supply and demand. It unpacks the tradeoffs between internal and external evaluation, and challenges some commonly held assumptions about both. Approach: Based on experiences as an internal evaluator, external evaluator, evaluation manager, and building evaluation capacity, the author explores how each role changes when evaluation is a scarce skill, and looks at implications outsourcing has for both the organization, and the evaluation. Findings: The purpose of the evaluation must drive the decision to outsource. However, with changing models of collaboration, there may be hybrid options that allow organizations to build evaluation capacity. Practical implications: Organisations are faced with a trade-off between commissioning an evaluation, and building internal evaluation capacity. To better understand each approach, it is important to consider the purpose and context of the evaluation. This shifts some commonly held assumptions about internal and external evaluations. Re-examining these assumptions will help organizations make a more informed decision about an evaluation approach. Originality/value: The field of evaluation is particularly concerned with evaluation use. Most of the literature on this has focused on the approach of individual evaluators, and insufficient attention has been paid to the institutional architecture of the evaluation. This article considers how some of the organisational structures around an evaluation contribute to evidence use, and the case study of South Africa also shifts the focus to the central but overlooked role of context in the debate.